Pediatric healthcare professionals' opinions, attitudes, and vaccine hesitancy toward personal and children’s COVID-19 vaccination : COVID-19 vaccination hesitancy among pediatric healthcare professionals - Tubaş, Filiz; Şener Taplak, Ayşe; Tatar, Sena Berra (Journal of Surgery and Medicine, 2022)
Background/Aim: Pediatric healthcare professionals are at the forefront of both facilitating an increase vaccine acceptability and reduction in vaccine hesitancy and play a vital role in eliminating vaccine hesitancy of families. In this context, it was thought that the individual pediatric healthcare professional’s vaccine hesitancy could affect successful administration of the coronavirus 2019 (COVID-19) vaccination. This study aimed to determine the opinions and attitudes of pediatricians and pediatric nurses toward the COVID-19 vaccination and the reasons for vaccine hesitancy. The study also aimed to identify their views and attitudes toward COVID-19 vaccination in children. Methods: The survey was carried out as a cross-sectional study between February and May 2021. The study sample consisted of 83 pediatricians and 79 pediatric nurses. Necessary permission was obtained before the study began. Data were collected using questionnaires that had been prepared by researchers. Data were analyzed using descriptive statistical methods and a chi-squared test. Results: Almost all pediatricians and more than half of the pediatric nurses reported that they considered getting vaccinated/were vaccinated; however, a greater proportion of nurses were vaccine-hesitant (P = 0.001). Reasons for not being vaccinated/being hesitant among healthcare professionals included harmful ingredients in the COVID-19 vaccines, thinking that vaccines were developed too quickly, vaccine development studies in different phases did not yield conclusive outcomes, hearing from the social media that vaccines are harmful, believing it is not necessary to receive a vaccine that is not included in the routine immunization schedule, and lack of knowledge about vaccines. The majority of the physicians and nurses who participated in the study reported that, if COVID-19 vaccines were available for children, they would not consider advising it or were unsure (P = 0.003). When asked about the reasons for hesitancy, a greater proportion of nurses reported they thought that vaccines had been developed too quickly (P < 0.001) and that the outcomes of vaccine development studies in different phases were not conclusive (P = 0.008). Conclusion: Healthcare workers serve as role models for vaccination acceptance in the community. Identifying the reasons for vaccine hesitancy among healthcare professionals is key to encouraging vulnerable populations to accept and take the vaccine. Vaccine hesitancy may be countered by comprehensive in-service trainings on vaccine development processes and phases of trials relating to COVID-19 vaccines.